ANALISIS ISI PESAN DAKWAH HABIB SYECH BIN ABDUL QODIR ASSEGAF MELALUI MEDIA SOSIAL INSTAGRAM - A'ourika Devi; Ulfah Dwi Hidayah; Muiz Al Barudin; Dwi Parwati (Academica : Journal of Multidisciplinary Studies, 2021)
The development of the era as it is currently experiencing a lot of development. Especially in the field of technology. Humans are increasingly making it easier to obtain information with digital advances. Almost all circles use the results of digital progress, the internet is one of them. With the internet, humans can access social media easily. There are so many uses of social media, one of which is Instagram, which is now widely used as a means of da'wah. This study was to find out the contents of Habib Syech Bin Abdul Qodir Assegaf's preaching message through Instagram Social Media with the @syaikhassegaf account. This research is included in qualitative research using descriptive method with content analysis techniques. Which includes: da'wah messages, methods and styles of delivery and the response of followers from the @syaikhassegaf account. The data collection techniques used in this study were words, videos and photos from the @syaikassegaf. In this study, it was found that the contents of the da'wah messages conveyed in the @syaikhassegaf instagram account included morals and worship.Keywords: Da’wa Massage; Instagram; Social Media